2021
DOI: 10.1002/cam4.4086
|View full text |Cite
|
Sign up to set email alerts
|

Quality of patient‐reported outcomes in oncology clinical trials using immune checkpoint inhibitors: A systematic review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, adverse effects were the cause of 20% of patients stopping treatment, the most common being rash, fatigue, or weight loss. Several studies have shown that the impact of adverse effects reported by participants in clinical trials is understated for both molecular and immunotherapies [15][16][17][18][19]. A systematic review by Peron and colleagues showed that 90% of 325 randomized controlled trials (RCTs) did not adhere to the Consolidated Standards of Reporting Trials (CONSORT) guidelines in the reporting methodology of adverse event collection [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects were the cause of 20% of patients stopping treatment, the most common being rash, fatigue, or weight loss. Several studies have shown that the impact of adverse effects reported by participants in clinical trials is understated for both molecular and immunotherapies [15][16][17][18][19]. A systematic review by Peron and colleagues showed that 90% of 325 randomized controlled trials (RCTs) did not adhere to the Consolidated Standards of Reporting Trials (CONSORT) guidelines in the reporting methodology of adverse event collection [16].…”
Section: Discussionmentioning
confidence: 99%
“…We herein report the results for the subset of patients with high-grade serous ovarian carcinoma (HGSOC) histology. We additionally included patientreported outcome (PRO) assessments, which have been poorly explored in immunotherapy clinical trials, [10][11][12] to better understand patient experience and quality of life (QOL) throughout this trial.…”
Section: Introductionmentioning
confidence: 99%
“…5 Regulatory agencies have recognized the value and challenges of incorporating COAs in drug development, 7,8 and multiple initiatives and guidelines for trial design, analysis, and reporting advocate for the use of COAs across clinical research. [9][10][11][12] PRO use has been evaluated in general oncology trials and focused cancer trial subsets [13][14][15][16][17][18] but the comprehensive use of COAs in oncology trials across time and how it compares to the use of COAs in non-oncology clinical trials has not been evaluated. Moreover, trends in relation to landmark regulatory and advocacy events have not been assessed, and with few exceptions 19,20 previous evaluations relied on manual curation of the literature which is not feasible for periodic assessments.…”
Section: Introductionmentioning
confidence: 99%
“…PRO use has been evaluated in general oncology trials and focused cancer trial subsets 13 , 14 , 15 , 16 , 17 , 18 but the comprehensive use of COAs in oncology trials across time and how it compares to the use of COAs in non‐oncology clinical trials has not been evaluated. Moreover, trends in relation to landmark regulatory and advocacy events have not been assessed, and with few exceptions 19 , 20 previous evaluations relied on manual curation of the literature which is not feasible for periodic assessments.…”
Section: Introductionmentioning
confidence: 99%